Artificial Intelligence in an Integrated Management System in Aviation - Knez, Sandi; Šprajc, Polona; Jandreoski, Goran; Željko Županič, Franc (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
This paper examines the impact of artificial intelligence (AI) on the integrated management system (IMS) in the aviation industry. The study highlights key advantages of AI, such as predictive maintenance, process automation, and enhanced safety through real-time data analysis. It also addresses significant challenges, including the explainability limitations of AI systems, their constraints in unpredictable situations, and ethical and legal issues such as accountability and data protection. The study recommends a synergy between AI and human intelligence, where AI supports operational processes while human oversight remains essential for critical decision-making. This research contributes to a better understanding of the challenges and opportunities brought by AI and provides guidance for its safe and effective implementation in the aviation sector.